Sporting subalternities and social justice: rethinking South African sports studies - Kaur, Tarminder; Akindes, Gerard (Acta Academica: Critical views on society, culture and politics, 2018)
In asking: ’How does sport help us better understand the richness and complexities of African experiences, in the past and present?’, Peter Alegi (2014) sets out an agenda for a field of research, we call: Sports Africa. Over the past three decades, study of sports in African Studies has gained some recognition with its own body of knowledge and debates.